Contrasting Effects of Fasting on Liver-Adipose Axis in Alcohol-Associated and Non-alcoholic Fatty Liver - Rasineni, Karuna; Jordan, Clayton W.; Thomes, Paul G.; Kubik, Jacy L.; Staab, Elizabeth M.; Sweeney, Sarah A.; Talmon, Geoffrey A.; Donohue, Terrence M.; McNiven, Mark A.; Kharbanda, Kusum K.; Casey, Carol A. (Frontiers in Physiology, 2021)
Background: Fatty liver, a major health problem worldwide, is the earliest pathological change in the progression of alcohol-associated (AFL) and non-alcoholic fatty liver disease (NAFL). Though the causes of AFL and NAFL differ, both share similar histological and some common pathophysiological characteristics. In this study, we sought to examine mechanisms responsible for lipid dynamics in liver and adipose tissue in the setting of AFL and NAFL in response to 48 h of fasting. Methods: Male rats were fed Lieber-DeCarli liquid control or alcohol-containing diet (AFL model), chow or high-fat pellet diet (NAFL model). After 6–8 weeks of feeding, half of the rats from each group were fasted for 48 h while the other half remained on their respective diets. Following sacrifice, blood, adipose, and the liver were collected for analysis. Results: Though rats fed AFL and NAFL diets both showed fatty liver, the physiological mechanisms involved in the development of each was different. Here, we show that increased hepatic de novo fatty acid synthesis, increased uptake of adipose-derived free fatty acids, and impaired triglyceride breakdown contribute to the development of AFL. In the case of NAFL, however, increased dietary fatty acid uptake is the major contributor to hepatic steatosis. Likewise, the response to starvation in the two fatty liver disease models also varied. While there was a decrease in hepatic steatosis after fasting in ethanol-fed rats, the control, chow and high-fat diet-fed rats showed higher levels of hepatic steatosis than pair-fed counterparts. This diverse response was a result of increased adipose lipolysis in all experimental groups except fasted ethanol-fed rats. Conclusion: Even though AFL and NAFL are nearly histologically indistinguishable, the physiological mechanisms that cause hepatic fat accumulation are different as are their responses to starvation.